Entrepreneurial intention: an empirical study of community college students in Malaysia. - Baharu Kemat AlHaj; Mohammed Zain Yusof; Nita Edama (Pusat Perkembangan Pelajar ,U.K.M, 2011)
The objective of the study is to identify the entrepreneurial intention among college community students in malaysia. A study was designed to determine the relationship of entrepreneurial intention antecedents perceived desirability, perceived feasibility and propensity of proative behaviour with entrepreneurial intention. The study was carried out in 17 college communities in Malaysia and 253students were involved to complete a structured questionnaire. The questionnaire was divided into six sections which include propensity of proactive behaviour, perceived desirability, perceived feasibility, breadth of entrepreneurial experience and positive entrepreneural experience, entrepreneural intention and the demografic factors. The analysis shows that the respondents have high in entrepreneurial intention. In this study shows that perceived desirability and propensity of proactive behaviour have positive relationship with the entrepreneurial intention. However. the ananlysis shows that perceived feasibility does not have a positive relationship with the entrepreneurial intention. In addition to that,the study would also like to see the relationship of the breadth of entrepneurial experience and positive entrepreneurial experience with those three indenpendent variables. This research proposed one model od entrepreneurial intention which uses theoretical framework mainly from Ajzen-Fishbeins intention theory (1980),Shaperos intention model (1982, entrepreneurial intention by Kruger and Carsrud (1993) and the theory of proactive personality by bateman and crant (1993). The Study can provide feedback to the management in order to improve the entrepreneurial programme and trainning which can increase the level of entrepreneurial intention among college community students in Malaysia.